Playing Ludomotor Activities in Lleida During the Spanish Civil War: An Ethnomotor Approach - Ormo-Ribes, Enric; Lavega-Burgués, Pere; Rodríguez-Arregi, Rosa; Luchoro-Parrilla, Rafael; Rillo-Albert, Aaron; Pic, Miguel (Frontiers in Psychology, 2021)
The traditional ludomotor activities (LA) are recognised by UNESCO as intangible cultural heritage of humanity. The ethnomotricity analyzes the LA in its sociocultural context, taking into account the proprieties of rules or motor conditions (internal logic) and the link with local culture (external logic). The aim of this research was to reveal the distinctive ethnomotor features of LA in order to know the adaptations produced in the social scenario of the Spanish Civil War (1936-1939) in Lleida. The corpus of the research was constituted by 101 LA, collected from the analysis of 20 semi-structured interviews. An "ad hoc" tool was designed, agreed upon by expert observers, constituted by 27 ethnomotor variables in the LA. The experts achieved high reliability when the classification of LA was carried out in two different moments. SPSS v.25 was used to apply descriptive statistics, cross-tabulations (Pearson's chi-squared) effect sizes, and two steps clusters by treating the set of external and internal logic variables as interlinked units of a binary set. The presence or absence of motor interaction (X 2 = 9.029; p < .003; ES = .298) was enlightening when comparing LA with and without war connotation. On the other hand, the hierarchy of variables rested primarily on IL-Domain (Psycho-Coop-Oppo-Coop/Oppo) (PI= 1). Among other singularities, while two-step cluster analysis revealed a corresponding ethnomotor silhouette with cluster 1, with warlike connotation (n = 48; 96.0%); in the opposite sense, its homologous was expressed (Cluster 2), in absence of the warlike character (n = 26; 50%).